Search & rescue - Ollhoff, Jim (Minneapolis, MN : ABDO Pub., 2013)
Presents information about search and rescue workers and volunteers, including different places where they may perform rescues, the equipment required, and how they use rescue dogs.
Search & rescue -- Search & rescue training -- Search & rescue gear -- Ground search & rescue -- Air-sea search & rescue -- Mountain search & rescue -- Urban search & rescue -- Search & rescue with dogs -- Interview with a search & rescue personnel -- FEMA.
Includes index.
Keywords: Search and rescue operations; Volunteer workers in search and rescue operations; Search and rescue operations; Volunteer workers in search and rescue operations